REKRUTMEN PROGRAM MANAGEMENT TRAINEE LEMBAGA INDEPENDEN (Studi Kualitatif Deskriptif Dengan NVivo 12 Plus) - Eka Nur Yati (2023)
Management Trainee is one of the recruitment programs organized by the Mandiri Institute. However, the Management Trainee program which was held twice by the Mandiri Institute resulted in a 50% difference in the number of recruits, so this phenomenon became a problem that was investigated in the case of recruitment through a program. This research is a qualitative research that aims to find out how the implementation process and recruitment series in the Management Trainee program are held by independent institutions to answer the phenomenon of these differences. Data collection in this study was carried out by interview, observation, and documentation methods. Interviews were conducted in a structured and semi-structured manner with five informants, including HR Recruitment Staff, Management Trainee Staff I, Management Trainee Staff II, and the Head of the Public Communications Team. To prove the validity of the data in this study, researchers used data triangulation. Furthermore, the data was analyzed using NVivo 12 Plus Software by reducing data, presenting data, and drawing conclusions. The results of the study found that substantively there were no differences in any aspect of the Management Trainee program, it's just that there were directions from the leadership regarding changes in employee qualifications that were adjusted to the needs of employees in various work units.